Dust grain dynamics due to nonuniform and nonstationary high-frequency radiations in cold magnetoplasmas - A. K. Nekrasov; F. Z. Feygin (Annales Geophysicae, 2006)
A general nonlinear theory for low-frequency electromagnetic field generation due to high-frequency nonuniform and nonstationary electromagnetic radiations in cold, uniform, multicomponent, dusty magnetoplasmas is developed. This theory permits us to consider the nonlinear action of all waves that can exist in such plasmas. The equations are derived for the dust grain velocities in the low-frequency nonlinear electric fields arising due to the presence of electromagnetic cyclotron waves travelling along the background magnetic field. The dust grains are considered to be magnetized as well as unmagnetized. Different regimes for the dust particle dynamics, depending on the spatio-temporal change of the wave amplitudes and plasma parameters, are discussed. It is shown that induced nonlinear electric fields can have both an electrostatic and electromagnetic nature. Conditions for maximum dust acceleration are found. The results obtained may be useful for understanding the possible mechanisms of dust grain dynamics in astrophysical, cosmic and laboratory plasmas under the action of nonuniform and nonstationary electromagnetic waves.